A Low‐Toxic Multifunctional Nanoplatform Based on Cu9S5@mSiO2 Core‐Shell Nanocomposites: Combining Photothermal‐ and Chemotherapies with Infrared Thermal Imaging for Cancer Treatment. (9th April 2013) - Song, Guosheng; Wang, Qian; Wang, Yang; Lv, Gang; Li, Chun; Zou, Rujia; Chen, Zhigang; Qin, Zongyi; Huo, Keke; Hu, Ronggui; Hu, Junqing
Abstract Copper chalcogenides have been demonstrated to be a promising photothermal agent due to their high photothermal conversion efficiency, synthetic simplicity, and low cost. However, the hydrophobic and less biocompatible characteristics associated with their synthetic processes hamper widely biological applications. An alternative strategy for improving hydrophilicity and biocompatibility is to coat the copper chalcogenide nanomaterials with silica shell. Herein, the rational preparation design results in successful coating mesoporous silica (mSiO2) on as‐synthesized Cu9S5 nanocrystals, forming Cu9S5@mSiO2‐PEG core‐shell nanostructures. As‐prepared Cu9S5@mSiO2‐PEG core‐shell nanostructures show low cytotoxicity and excellent blood compatibility, and are effectively employed for photothermal ablation of cancer cells and infrared thermal imaging. Moreover, anticancer drug of doxorubicin (DOX)‐loaded Cu9S5@mSiO2‐PEG core‐shell nanostructures show pH sensitive release profile and are therefore beneficial to delivery of DOX into cancer cells for chemotherapy. Importantly, the combination of photothermal‐ and chemotherapies demonstrates better effects of therapy on cancer treatment than individual therapy approaches in vitro and in vivo.